Effects of Nigella sativa and Hypericum perforatum on wound healing - Han, Mehmet Cengiz; Durmus, Ali Said; Sagliyan, Aydin; Gunay, Cihan; Ozkaraca, Mustafa; Kandemir, Fatih Mehmet; Oztopalan, Dicle Firat (Tubitak Scientific & Technological Research Council Turkey, 2017)
In this study, it was aimed to determine the influence of applying Nigella sativa (NS) and Hypericum perforatum (HP) on wound healing. A total of 42 female albino 2-month-old Wistar rats were randomly separated into 3 main groups. Each of these main groups was separated into two subgroups for 7-and 14-day postoperative follow-ups. A total of 84 excisional skin wounds, 5 mm in diameter, were created on the backs of the rats. Placebo cream (control group), 50% NS oil cream, and 50% HP oil cream were applied topically for the first, second, and third group, respectively. The wounds were checked daily. Seven rats from each group were euthanized on the 7th and 14th days after the operation. Skin samples taken from wound areas were examined histologically and biochemically. The measurements revealed that the wounds healed faster in the study groups than in the control group (P < 0.001). It was found that NS had more antioxidant properties than the other treatments, and HP increased wound healing via its positive effects on epithelialization and granulation. The clinical, biochemical, and histological findings showed that NS and HP increased the healing of skin wounds.
Keywords: Nigella sativa; Hypericum perforatum; wound healing; rat